Potentials of constrained sliding mode control as an intervention guide to manage COVID19 spread. (May 2021) - Nuñez, Sebastián; Inthamoussou, Fernando A.; Valenciaga, Fernando; De Battista, Hernán; Garelli, Fabricio
Highlights: Non-pharmaceutical interventions (NPIs) are key tools to fight the COVID-19 disease. Sliding mode reference conditioning is evaluated as a guide for NPI design. Reduction in contact rate is pursued to avoid intense care units' capacity saturation. Constraint level for the infectious population and the approaching rate can be tuned. Realistic piece-wise discretized control actions show applicability of the proposal. Abstract: This work evaluates the potential of using sliding mode reference conditioning (SMRC) techniques as a guide for non-pharmaceutical intervention (NPI) to control the COVID-19 pandemic. In particular, for the epidemiological problem addressed here, it is used to compute the contact rate reduction requirement in order to limit the infectious population to a given threshold. The SMRC controller allows the desired output variable limit and its approaching rate to be tuned explicitly. Implementation issues are taken into account and a periodically update of the NPI is proposed for the real life application. The strategy is evaluated under different scenarios where its distinctive features are exhibited.